Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given f(x)=2x+3 and g(x)=3x, find the following combinations: g(x)+f(x)
g(x)-f(x)
Please show and explain all work.


Sagot :

g(x) + f(x) =  2x + 3 + 3x = (2x + 3x) +3  = 5x + 3

g(x) - f(x)= 2x + 3 - 3x = (2x - 3x) + 3 = 3 - x

ok done. Thank to me :>